Evaluasi Kesesuaian Lahan untuk Komoditas Padi dengan Memanfaatkan Aplikasi Sistem Informasi Geografis (SIG) di Kabupaten Lombok Tengah - Fitriani Risti Fauzi; Sirajuddin Haji Abdullah; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Land suitability evaluation for agricultural commodity can be arranged based on land condition. Since every plants type have a spesific growth requirement that suitable with the region characteristic, to grow and rise optimally. The aim of this research was to determine level of suitability land for "Sawah" rice and "Gogo" rice in Lombok tengah region base on some aspect, i.e. topography, soil type, and climate. This research also conducted to determine land characteristic in Central Lombok Regency. The method used in this research was by matching the region land condition data with the existence land suitability class criteria for "Sawah" rice and "Gogo" rice. Land suitability evaluation maps was arranged by using ArcView GIS 10.5. Observed parameters were land characteristic and level of land suitability for "Sawah" rice and "Gogo" rice in Central Lombok Regency. Generally, Central Lombok Regency with area 1.208,39 kmÂ² has elevation about 0-3000 meters above sea water level and slope level range from 0 (zero) to more than 150%. Based on type of soil, i.e. drainage, Central Lombok Regency was dominated by impeded drainage, good drainage and medium drainage. Land texture was dominated by sandy loam, loam, clay loam and clay with landâ€™s effective depth range from 80-120 cm, while the pH of the land range from 5-8. The precifitation of this area range from 1.000-3.000 mm/year. The level of land suitability for "Sawah" rice in Central Lombok Regency and its area are very suitable (S1) covers 298.203 Ha, moderately suitable (S2) covers 1013.165 Ha, marginally suitable (S3) covers 64828.164 Ha, currently suitable (N1) covers 20832.869 Ha, permanently not suitable (N2) covers 20524.485 Ha. The level of land suitability for "Gogo" rice in Central Lombok Region and its area are very suitable (S1) covered 0, moderately suitable (S2) covered 34485.186 Ha, marginally suitable (S3) covered 64828.164 Ha, currently suitable (N1) covered 4591.509 Ha, permanently not suitable (N2) covered 13260.590 Ha.